Emotional Labor, Social Support, and Posttraumatic Growth as Factors Associated with Depression and Anxiety in Elementary School Teachers: A Cross-Sectional Study. - Im, Seon-Jeong; Oh, Hee-Joo; Kim, Suk-Sun (Journal of Korean Academy of Psychiatric & Mental Health Nursing (JKPMHN), 2025)
Purpose: This study aimed to investigate the relationships among emotional labor, social support, posttraumatic growth, depression, and anxiety, as well as to identify predictors of depression and anxiety in elementary school teachers. Methods: Data were collected from 155 elementary school teachers utilizing structured self-report questionnaires. The data analysis employed descriptive statistics, independent t-tests, one-way ANOVA, Pearson's correlation coefficients, and multiple regression analysis, conducted using IBM SPSS Statistics 29.0. Results: Depression and anxiety exhibited positive correlations with subscales of emotional labor, including the frequency of emotional display, attentiveness to display rules, and emotional dissonance. Conversely, these mental health outcomes were negatively associated with perceived social support from family, friends, and significant others, as well as with posttraumatic growth. Multiple regression analysis indicated that emotional dissonance constituted a significant risk factor for both depression and anxiety, whereas family support and posttraumatic growth functioned as protective factors. Additionally, religious affiliation emerged as a risk factor for depression. Conclusion: These findings suggest that interventions should focus on enhancing emotional regulation, family support, and posttraumatic growth to mitigate depression and anxiety among teachers. Furthermore, additional research is needed to elucidate the relationship between religious beliefs, spiritual struggles, and teachers' mental health.